Etiology and intensity of leaf spot in wheat cultivars at three sites at Rio Grande do Sul, Brazil - Durante Danelli, Anderson Luiz (2011)
This study aimed to identify and quantify the causal agents of fungal leaf blights, and compare different assessment methods for disease quantification. The experiments were conducted with 20 medium cycle cultivars in Passo Fundo, Saint Augustus and Vacaria counties with three replications in randomized blocks. For evaluation 20 leaves were collected per plot, at flowering stage. Disease severity was estimated by the percent diseased leaf area and lesions number per leaf. For fungus etiology, twenty five discs of each leaf sample containing a lesion were subjected to a humid chamber. After three days incubation fungi identification was performed under a dissecting microscope. The mean incidence, number of lesions and severity data were subjected to analysis of variance and means compared by the Tukey’s multiple test at 5% significance level. The severity and lesions number were the most efficient criteria to fungal foliar disease, predominantly Bipolaris sorokiniana, Drechslera siccans, D. tritici-repentis and Stagonospora nodorum. The cultivars with the highest incidence rates were not the same as that presented the greatest number of injuries and severity. Join the appearance D. siccans and the resurgence of S. nodorum.